Intersectionality : origins, contestations, horizons - Carastathis, Anna (Expanding frontiers: interdisciplinary approaches to studies of women, gender, and sexuality, 2016)
"Intersectionality critically examines the mainstreaming and institutionalization of this concept, offering a renewed understanding through close readings of some of its generative texts"--